2021
DOI: 10.1007/s12662-021-00724-8
|View full text |Cite
|
Sign up to set email alerts
|

Sex/gender considerations in school-based interventions to promote children’s and adolescents’ physical activity

Abstract: Physical inactivity is an increasing problem worldwide, but especially among girls. This difference by gender increases with age. Schools serve virtually all young people in most parts of the world and can thus play an important role in promoting physical activity. In this systematic review, we qualitatively and comprehensively assessed the treatment of sex/gender considerations (from study design to discussion of results) in 56 school-based intervention studies aiming to promote physical activity in children … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 59 publications
(91 reference statements)
1
6
0
Order By: Relevance
“…Regarding the second objective of the study, which aimed to compare levels of PA between genders before and during the pandemic, we found that, as in previous literature (Rodríguez-Fernández, Rico-Díaz, Neira-Martín, & Navarro-Patón, 2020;Schlund, Reimers, Bucksch, Linder, & Demetriou, 2021), males had significantly higher levels of PA than females, though only in the period before the pandemic. These results are in line with another Portuguese study that analysed PA during the COVID period, which showed similar levels of PA in both genders during the pandemic (Pombo et al, 2020).…”
Section: Discussionsupporting
confidence: 56%
“…Regarding the second objective of the study, which aimed to compare levels of PA between genders before and during the pandemic, we found that, as in previous literature (Rodríguez-Fernández, Rico-Díaz, Neira-Martín, & Navarro-Patón, 2020;Schlund, Reimers, Bucksch, Linder, & Demetriou, 2021), males had significantly higher levels of PA than females, though only in the period before the pandemic. These results are in line with another Portuguese study that analysed PA during the COVID period, which showed similar levels of PA in both genders during the pandemic (Pombo et al, 2020).…”
Section: Discussionsupporting
confidence: 56%
“…The finding that PA increased after the COVID-19 restrictions had been eased is in line with studies that compared children’s and adolescents’ PA upon return to school [ 58 , 59 ]. This is not surprising given that COVID-19 restrictions removed many opportunities for children and adolescents to be active, such as active travel to school, school break times, and sports activities in and out of the school context [ 36 , 37 ]. Furthermore, our analysis revealed no covariance between intercept and slope in the elevation of PA, indicating that the participants became more physically active after the pandemic regardless of how active (or inactive) they were during the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…The aim of this study, therefore, was to test the reciprocal relationship between PA and mental health in children and adolescents. Schools are widely recognized as essential for promoting PA in this target group [ 35 ], as the school setting provides many different opportunities for formal and informal PA, such as regular courses, active breaks between classes, or after-school programs [ 36 , 37 ]. We thus sampled school-aged children and collected data on their mental health problems, health-related quality of life, and PA both before and during the easing of COVID-19 restrictions.…”
Section: Introductionmentioning
confidence: 99%
“…Even so, as far as gender in PAL is concerned, gender is still rarely investigated in the field of preschool education. According to multiple review articles, Schlund et al (2021a), Schlund et al (2021b), Schulze et al (2021), and Kippe and Lagestad (2018) found that gender is inadequate in related studies to a large extent. Some identified affecting factors such as ethnicity (Hu et al, 2021), semester of birth (Navarro-Patón et al, 2021), and SEND also failed to be considered in the previous studies.…”
Section: Research Questionsmentioning
confidence: 99%